MENAFSIR KASIH DAN PENEBUSAN: REFLEKSI TEOLOGIS ATAS MAKNA SALIB DALAM KEHIDUPAN KRISTEN KONTEMPORER - Yospianita; Ikeshy Jurice Pauranan; Akhsa; Risal; Herniati Sirande (Adisam Publisher, 2026)
This article aims to examine the theological meaning of love and redemption in the event of the cross and its relevance for contemporary Christian life. The cross is understood not only as a symbol of suffering, but as an embodiment of God's love that saves and restores humanity's relationship with Him. Using a descriptive qualitative approach and literature study methods, this study analyzes various theological perspectives from relevant sources. The results of the study indicate that the cross contains dimensions of sacrificial love, transformative redemption, and divine solidarity in human suffering. Furthermore, the meaning of the cross has real ethical and spiritual implications in the lives of believers, such as forgiveness, sacrifice, and obedience. In the challenging modern context, the cross remains a source of hope and direction in life. Therefore, theological reflection on the cross is important to enrich contextual and relevant Christian spirituality.